Avaliação de sistemas de e-participação: uma abordagem centrada no cidadão - Gonçalves, Bruno da Silva (2016)
In the last decades, electronic government has assumed an important role in Public Administration. However, there are significant methodological and conceptual challenges for monitoring and evaluating the efficiency, effectiveness and acceptance of these projects. Despite the importance of evaluating e-government systems, there has been a lack of systematic studies on the evaluation methods of these systems. For this reason, a systematic review of the literature on methods of evaluation of e-government systems is presented as the first study of this dissertation. In this study, the results showed that current methods are limited in addressing subjective aspects of user experience such as emotion, affection, experience, value, pleasure, beauty and hedonic quality and civic feelings and their influence on civic participation, participation Politics, social trust, and institutional trust. To further the understanding of such issues in the context of e-government, an empirical study is presented, comparing the results of the evaluation of traditional e-government criteria with the results of the evaluation of the user experience in electronic participation systems and a study that makes a literature survey of items to measure the Civic engagement, political participation, social trust and institutional confidence of citizens. The empirical study showed that the constructs of the traditional method of evaluation of electronic government reasonably explain the constructs of the method of evaluation of the user experience. In the bibliographic study items were collected, which were grouped by the constructs civic experience, civic participation, political participation, social trust and institutional trust. Future studies are needed to produce an evaluation model of civic feelings for users of e-government systems.